1986
DOI: 10.24266/0738-2898-4.3.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wounding, IBA and Basal Trimming on Rooting of Boxwood Cuttings

Abstract: Wounding, indole butyric acid (IBA) and trimming of cuttings to a basal node were evaluated for their effects on rooting of Buxus sempervirens L. (American boxwood), B. sempervirens L. ‘Suffruticosa’ (English boxwood), B. microphylla var. koreana Nakai. (Korean boxwood), and B. microphylla var. japonica (Müll. Agr.) Rehd. and Wils. (Japanese boxwood) cuttings. Rooting of all cultivars was improved by a 5 second dip in a 0.4% aqueous solution of the potassium salt of IBA. Wounding the basal end of the cuttings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a result of the study, higher results were obtained in phytohormone-treated cuttings compared to control cuttings in terms of RP, RL and RN. Banko and Stefani (1986) reported that the longest root lengths obtained in B. sempervirens were 2.40 cm (nodal cuttings) and 2.60 cm (internodal cuttings) in the combination of wounding and IBA treatment. For B. sempervirens semi-hardwood cuttings, Vieira et al (2018) obtained the highest number of roots and the longest root length with 3.73 roots and 2.55 cm, respectively, in the control cuttings, while IBA 6,000 mgL -1 took the second place with 3.66 roots and 2.45 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the study, higher results were obtained in phytohormone-treated cuttings compared to control cuttings in terms of RP, RL and RN. Banko and Stefani (1986) reported that the longest root lengths obtained in B. sempervirens were 2.40 cm (nodal cuttings) and 2.60 cm (internodal cuttings) in the combination of wounding and IBA treatment. For B. sempervirens semi-hardwood cuttings, Vieira et al (2018) obtained the highest number of roots and the longest root length with 3.73 roots and 2.55 cm, respectively, in the control cuttings, while IBA 6,000 mgL -1 took the second place with 3.66 roots and 2.45 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Banko and Stefani (1986) on the cutting propagation of Buxus sempervirens, nodal (cuttings were cut just below a node) and internodal (cuttings were cut above a node) cuttings were used. They stated that the highest rooting percentage was determined as 78.5% in nodal cuttings that wounding and IBA combined application were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation